A Century of Nadhlatul Ulama’s Contribution to Modernizing Islamic Education in Indonesia - Munawir; Novita, Almi (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Nadhlatul Ulama (NU) has long prioritized the issue of education, recognizing its importance as the key to unlocking a better future. Holding onto religious values and harnessing the advancements in knowledge and technology, NU consistently designs transformations within its educational institutions to meet the challenges of the future. This study aims to explore NU’s role and significant contributions in the effort to modernize Islamic education and delve into its one-century existence as an entity contributing to the development of education in Indonesia. The Library Research method is employed in this study to gather and analyze various data sources, including books, journals, and other literature, which are then synthesized into a scholarly article. The research findings indicate that NU has endeavored to implement educational modernization through the establishment of thousands of educational institutions, especially pesantren, across Indonesia. The integration of modern education with digital learning tools is one concrete effort undertaken by NU to adapt to changing times. In addition to providing religious education, NU is committed to nurturing a generation that possesses a grasp of knowledge and technology, enabling them to compete in the era of globalization.